2021
DOI: 10.1017/s0033291720004870
|View full text |Cite
|
Sign up to set email alerts
|

The role of depressive symptoms and symptom dimensions in actigraphy-assessed sleep, circadian rhythm, and physical activity

Abstract: Background Considering the heterogeneity of depression, distinct depressive symptom dimensions may be differentially associated with more objective actigraphy-based estimates of physical activity (PA), sleep and circadian rhythm (CR). We examined the association between PA, sleep, and CR assessed with actigraphy and symptom dimensions (i.e. mood/cognition, somatic/vegetative, sleep). Methods Fourteen-day actigraphy data of 359 participants were obtained from the Netherlands Study of Depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
0
11
1
Order By: Relevance
“…They found a unidirectional association between motor activity and subjective mood level and a bidirectional association between motor activity and subjective energy level and sleep duration. Difrancesco et al ( 14 ) obtained similar results, with a negative correlation of gross motor activity (GMA) and sleep parameters with depressive symptoms. Tonon et al ( 15 ) demonstrate the reliability of using an actigraphic strategy for evaluating the intensity of depression.…”
Section: Resultsmentioning
confidence: 70%
“…They found a unidirectional association between motor activity and subjective mood level and a bidirectional association between motor activity and subjective energy level and sleep duration. Difrancesco et al ( 14 ) obtained similar results, with a negative correlation of gross motor activity (GMA) and sleep parameters with depressive symptoms. Tonon et al ( 15 ) demonstrate the reliability of using an actigraphic strategy for evaluating the intensity of depression.…”
Section: Resultsmentioning
confidence: 70%
“…Findings on physical activity are controversial. While some studies report preliminary evidence for lower physical activity ( Difrancesco et al, 2019 ) and a negative correlation between depressive symptom severity and physical activity in depressed individuals ( Difrancesco et al, 2021 ), another study found no such effects ( Lorenz et al, 2019 ).…”
Section: Circadian Regulation Of Behaviour and Cognitive Functioningmentioning
confidence: 99%
“…Disordered sleep also has a signi cant impact on cognitive ability, as has been shown in studies with children, with the elderly, and with victims of traumatic brain injury, among others (9). Reduced sleep quality can also increase emotional distress, mood swings, behavioral problems, and de cits in cognitive performance (10)(11)(12). The cumulative effect of disrupted sleep can lead to severe impairments in daytime wakefulness and cognitive functioning.…”
Section: Introductionmentioning
confidence: 96%